Isolamento, identificação e caracterização de leveduras isoladas do mirtilo - Lucion, Fernanda Bortoluzzi (2015)
The chemical profile of a fermented product depends upon the raw basic material and the fermentative microbiota. The yeast microbiota is responsible for fermentation and contributes to fermented product aroma by several mechanisms. The study of this microbiota is relevant because the microorganisms utilize the constituents of the raw basic material and transform them into aroma or flavour impacting components. Autochthonous yeasts belonging to the blueberry microbiota of two different cultivars, Florida M and Climax, were investigated by analyzing the fermentative capacity, the hydrogen sulfide (H2S) production, the film-forming ability, killer feature, sensitivity and neutrality to killer factor. Three methods employed to distinguish autochthonous yeast species were used: MALDI-TOF MS, PCR and PCR-RFLP of ITS region of rRNA gene and, if necessary, genetic sequencing of the D1/D2 26S rRNA region. The species Hanseniaspora uvarum, Hanseniaspora opuntiae, Candida sorboxylosa, Metschnikovia kunwiensis, Candida bentonensis, Candida oleophila/Candida railenesis and Candida quercitrusa were found on the surface of Florida M. Hanseniaspora uvarum, Issatchenkia terricola, Candida sorboxylosa, Candida asiatica, Candida oleophila/railenensis, Issatchenkia hanoiensis and Kazachstania intestinalis were of berries of Climax variety. Only three species were found in both varieties: H. uvarum, C. sorboxylosa and C. oleophila/railenensis. The species H. uvarum was the predominant in both cultivars, representing 70.4% and 78% of yeasts isolated from the surface of the Florida M and Climax, respectively. The killer feature was not detected in any strain isolated from Florida M. From strains isolated from Climax, only one strain C. asiatica 133 MCMCF/14 was killer against the 26B. Moreover, the K. intestinalis 91 MCMCF/14 was the only sensitive when tested against both the patterns killer S. cerevisiae K1 (Lallemand), EMBRAPA 1B, EMBRAPA 91B and the killer yeast C. asiatica 133 MCMCF/14. All strains showed low fermentative capacity and all of them were non-Saccharomyces yeasts. All yeasts isolated from Florida M produced H2S. Only four strains from Climax did not produce H2S. The highest evolution of H2S was observed with the genus Issatchenkia and with the majority strains of C. sorboxylosa. The species C. oleophila/C. railenensis showed low production of this parameter. The fermentation process of fermented products from blueberries of both Florida and Climax can be severely affected by this kind of autochthonous yeasts.